Prognostic value of the lymphocyte-albumin index combined with PSI score in predicting mortality in severe communityacquired pneumonia - Altuntaş, Gülsüm (My University, 2025)
Aim: Severe community-acquired pneumonia (SCAP) is a leading cause of sepsis, septic shock, and mortality. Various prognostic scoring systems are used for evaluation, but their use and availability may be complex. Our objective was to evaluate the prognostic significance of LAI, which is easy and inexpensive to perform, and the importance of its combination with PSI score in predicting the mortality of patients with SCAP. Materials and Methods: This is a retrospective, single-center, cross-sectional study. The patients aged ?18 with SCAP in tertiary intensive care units were analyzed. Data from patient files and the hospital database include demographic data, PSI score, SOFA, GCS, APACHE II, laboratory parameters, and clinical variables. Cut-off values were used to assess the predictive accuracy of each predictor, measured by the area under the ROC curve (AUC) with a 95% confidence interval (CI). Additionally, we developed combined models for PSI+LAI utilizing various logistic regression analyses. Factors associated with mortality were analyzed using multivariate logistic regression analysis. Results: The cut-off value of 110 for PSI was a good predictor with 97.8% sensitivity and 98.7% specificity. The cut-off value of 3379 for LAI was observed to be a good predictor of mortality with 92.5% sensitivity and 90.7% specificity. The AUC value for PSI was 0.987 and the AUC value for LAI was 0.933. The AUC value obtained when PSI and LAI values were evaluated together was 0.997. In multivariate analysis, high PSI score, low pulse rate, and LAI value constitute a risk for mortality. Conclusion: Although PSI or LAI have a high predictive accuracy, their combined use may improve this accuracy and allow for more reliable management of SCAP patients. The PSI score offers a comprehensive assessment. This, combined with the faster and easier application of LAI, provides great advantages to clinicians.
Keywords: Prediction; Intensive care units; Pneumonia severity index; Lymphocyte albumin index; Severe community-acquired pneumonia